Astronomical calibration and global correlation of the Santonian (Cretaceous) based on the marine carbon isotope record. (29th June 2016) - Thibault, N.; Jarvis, I.; Voigt, S.; Gale, A. S.; Attree, K.; Jenkyns, H. C.
Abstract: High‐resolution records of bulk carbonate carbon isotopes have been generated for the Upper Coniacian to Lower Campanian interval of the sections at Seaford Head (southern England) and Bottaccione (central Italy). An unambiguous stratigraphic correlation is presented for the base and top of the Santonian between the Boreal and Tethyan realms. Orbital forcing of carbon and oxygen isotopes at Seaford Head points to the Boreal Santonian spanning five 405 kyr cycles (Sa1 to Sa5). Correlation of the Seaford Head time scale to that of the Niobrara Formation (Western Interior Basin) permits anchoring these records to the La2011 astronomical solution at the Santonian‐Campanian (Sa/Ca) boundary, which has been recently dated to 84.19 ± 0.38 Ma. Among the five tuning options examined, option 2 places the Sa/Ca at the 84.2 Ma 405 kyr insolation minimum and appears as the most likely. This solution indicates that minima of the 405 kyr filtered output of the resistivity in the Niobrara Formation correlate to 405 kyr insolation minima in the astronomical solution and to maxima in the filtered δ 13 C of Seaford Head. We suggest that variance in δ 13 C is driven by climate forcing of the proportions of CaCO3 versus organic carbon burial on land and in oceanic basins. The astronomical calibration generates a 200 kyr mismatch of the Coniacian‐Santonian boundary age between the Boreal Realm in Europe and the Western Interior, due either to diachronism of the lowest occurrence of the inoceramid Cladoceramus undulatoplicatus between the two regions or to remaining uncertainties of radiometric dating and cyclostratigraphic records. Key Points: New Upper Coniacian‐Lower Campanian high‐resolution carbon and oxygen isotope records for the English Chalk Astronomical calibration and global correlation of the Santonian stage The 405 kyr insolation forcing of carbon isotope variations via CaCO3 versus Corg burial on land and in oceanic basins